An exploratory study of first year residence students' perceptions regarding safety and security at the University of Cape Town - Kahari, Ingrid (2010)
Includes abstract.Includes bibliographical references (leaves 76-82).Safety and security is an issue that institutions of higher learning have to deal with and address within their campuses. The focus of this study was to explore first year residence students perceptions regarding safety and security at the University of Cape Town (UCT). An exploratory qualitative approach was used in this study. The purposive sample consisted of fourteen first year students from three UCT residences and three residence supervisors from these residences giving a total sample of seventeen participants. The results of the study showed that students see themselves as safer within the confines of UCT whereas they feel relatively unsafe off campus